PERTUMBUHAN AWAL LIMA KLON TEBU (Saccharum officinarum L.) DI TANAH ULTISOL, VERTISOL, DAN REGOSOL - , WULAN DWI PRASASTI; , Dr.Ir. Taryono, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Domestic sugar demand uses to increase, whereas sugarcane productivity always decrease. The decreasing sugarcane productivity due to the shifting of sugarcane cultivation area from paddy fields to dry land. Planting sugar cane on dry land should consider several requirements include soil type. The research is intended to study the growth of five sugarcane clones in Ultisol, Vertisol, and Regosol soil types. The research was conducted at the Banguntapan Experimental Station, Faculty of Agriculture, Gadjah Mada University, Yogyakarta, stating on November 2012 up to April 2013. experiment th Research using 3x5 factorial at was arranged in Completely Randomized Design with three replications. The first factor was soil types consist of Ultisol, Vertisol, and Regosol, while the second factor was sugarcane clones consist of PSJT-941, VMC 86-550, BL, PS-881, and PS-864. There were three polybag containing one growing sugarcane plant in each polybag in each experimental unit. The observation variables includes plant height, leaf number, stem diameter, seedlings, internode number, total fresh weight, shoot fresh weight, root fresh weight, leaf area, total dry weight, shoot dry weight, root dry weight, shoot root ratio, root volume, and root surface area. The result showed that there was an interaction between soil types and sugarcane clones on leaf number, stem diameter, internode number, total fresh weight, shoot fresh weight, and root fresh weight. Based on regression approach and GGE Biplot on total fresh weight and the leaf number, PS 864 was categorized as a wide adapted clone. The other result showed that PSJT-941 clone performed well in fertile soil type such as Regosol.